PERTANGGUNGJAWABAN PIDANA PAGUYUBAN PADA TINDAK PIDANA PERDAGANGAN ORANG ( STUDI PUTUSAN NO. 724 / PID. SUS/ 2014/PN. JKT. UTR DAN PUTUSAN NO. 725 / PID. SUS/ 2014/PN. JKT. UTR) - Fahmi Tanjung; Alvi Syahrin; Muhammad Hamdan; Muhammad Ekaputra (Universitas Sumatera Utara, 2018)
This research analyzed the Ruling No.724/Pid.Sus/2014/PN Jkt.Utr and the Ruling No.725/Pid.Sus/2014/PN Jkt.Utr which involve two associations which are proved to be guilty of committing human trafficking as it is stipulated in Article 2, paragraph (1) in conjunction with Article 13, paragraph (1) of Law No. 21/2007 on the Eradication of Human Trafficking Criminal Act. Constructing the criminal liability of associations is firstly by determining its objective culpability; if there is any objective culpability, it is followed by subjective culpability in their management and the members that include liability, normative errors, and no reason for forgivingness. The identification and aggregation of subjective culpability of the management and the members will be distributed to be the association’s subjective culpability. In the liability of the two associations in the two Rulings, the judge imposes the liability upon the management and the members individually of Bina Jasa Mina association in which the judge uses the two systems of criminal liability of corporation in which Bina Jasa Mina corporation commits it and the management takes responsibility. Keywords: Criminal Liability, Association, Human Trafficking